Sustainable Energy Policies and Equality: Is There a Nexus? Inferences From the Analysis of EU Statistical and Survey Data - Pellegrini-Masini, Giuseppe; Egner, Lars Even; Klöckner, Christian Andreas; Löfström, Erica (Frontiers in Sustainable Cities, 2021)
Energy Justice (EJ) and particularly Energy equality (EE), arguably a radical conceptualization of energy justice, advocated for distributional justice and policies addressing distributional inequalities. Distributional policies are known to be contentious and often raise debates on the opportunity to interfere with the free-market allocation of goods in capitalistic economies. Whether EE inspired policies might be considered implementable or not depends on their social acceptability. Therefore, holding on to previous research findings pointing to the higher acceptability of equitable climate policies and the relationship between economic inequality and environmental degradation, we analyse EU data regarding income and income and wealth inequality and data from the H2020 ECHOES project, which consists of an extensive European survey of household energy consumption attitudes. We found that economic equality accounts for 41% of the variance explained at the country level of our sustainable energy care index (SECI), accounting for sustainable energy attitudes. We conclude that the interplay between economic equality and sustainable energy attitudes deserves further attention and might warrant a broader discussion about distributive policies within and beyond the energy sector.